2001
DOI: 10.1111/0938-8982.00003
|View full text |Cite
|
Sign up to set email alerts
|

Can Middle School Students with Serious Reading Difficulties Help Each Other and Learn Anything?

Abstract: This investigation was intended to examine the effects of teaching middle school students with learning disabilities and mild mental retardation to tutor one another in reading comprehension strategies. All students were reading significantly below grade level and many students exhibited behavior problems in addition to their primary disability area. Students were randomly assigned to a tutoring or traditional reading instruction condition. Within the tutoring condition, students were matched into tutoring dya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(127 citation statements)
references
References 12 publications
6
117
2
1
Order By: Relevance
“…Encouragingly, these results differ from previous studies which demonstrated small gains for adolescents in reading fluency (Calhoon, 2005;Edmonds et al, 2009;Fuchs, Fuchs, & Kazdan, 1999;Olson, Wise, Johnson, & Ring, 1997;Mastropieri et al, 2001). A reason for the fluency gains, seen by all modules, could be attributed to the gains in linguistics skill knowledge.…”
Section: Fluency Skillscontrasting
confidence: 99%
“…Encouragingly, these results differ from previous studies which demonstrated small gains for adolescents in reading fluency (Calhoon, 2005;Edmonds et al, 2009;Fuchs, Fuchs, & Kazdan, 1999;Olson, Wise, Johnson, & Ring, 1997;Mastropieri et al, 2001). A reason for the fluency gains, seen by all modules, could be attributed to the gains in linguistics skill knowledge.…”
Section: Fluency Skillscontrasting
confidence: 99%
“…For example, friendships provide socioemotional resources when an adolescent derives comfort and support from friends, which enhance self-image and identity development, or when an adolescent's popularity among friends enhances his or her social status in the network (Eder 1985). As another example, friendships provide instrumental resources when an adolescent receives help with coursework from friends or when friendships provide a power base from which to rebel against adults (Hartup 1989;Hallinan and Williams 1990;Alfassi 1998;Fuchs, Fuchs, and Kazdan 1999;Mastropieri et al 2001;Waltemeyer and Balfanz 2002;Crosnoe et al 2003;McFarland 2004;Riegle-Crumb et al 2006). …”
mentioning
confidence: 99%
“…Este modelo no es eficaz, en particular en aulas inclusivas. Sin embargo, adoptando enfoques constructivistas, una enseñanza de las ciencias para alumnos con discapacidades físicas e intelectuales es posible y beneficiosa (Mastropieri et al 2001). Una de estas metodologías es la indagación.…”
Section: Fundamentación Teóricaunclassified